Kinetics of dehydrogenation of n-heptane over GaPt supported catalytically active liquid metal solutions (SCALMS) - Oshin, Oshin; Al-Shaibani, Asem; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter (Reaction Chemistry & Engineering, 2024)
The concept of Supported Catalytically Active Liquid Metal Solutions (SCALMS) was explored for the catalytic dehydrogenation of n-heptane. For this purpose, a GaPt on alumina (Ga84Pt/Al2O3) was compared with a Pt on alumina catalyst at different reaction temperatures and feed compositions. While the observed activation energies with both catalysts for the overall n-heptane depletion rate were similar with both catalysts, the SCALMS systems provides a lower activation energy for the desired dehydrogenation path and significantly higher activation energies for the undesired aromatization and cracking reaction. Thus, the SCALMS catalyst under investigation shows technically interesting features, in particular at high temperature operation. The partial pressure variation revealed an effective reaction order of around 0.7 for n-heptane for both catalysts, while the effective order for hydrogen was 0.35 for Pt/Al2O3 and almost zero for SCALMS.
CRIS-Team Scopus Importer:2024-02-16